The creation of flipbook-based electronic teaching modules using the Heyzine website on Static Electricity Material for Class XII Students - Dwi Ramdhani, Novian (Master of Physics Education Study Programme, 2025)
This research aims to develop physics teaching materials based on electronic teaching modules on static electricity in class. This research uses a research and development method (Research & Development) which refers to the 4D Model with 4 stages including the definition stage, design stage, development stage and deployment stage. The result of this research is an electronic teaching module which is expected to make it easier for teachers in the learning process and attract students' interest in independent learning.